The Effect of Using Critical Thinking Activities on Knowledge Monitoring in Science of Seventh Graders in the Sultanate of Oman - Ibrahim S. Al-Harthy; Abdullah K. Ambusaidi (Sultan Qaboos University, 2016)
The aim of the current study was to investigate the effects of using critical thinking activities in the classroom to enhance and develop students' knowledge monitoring and whether knowledge monitoring predicts students' academic achievement in Science. Fifty females were randomly selected from the seventh grade at one of Al-Saeeb province schools in Muscat governorate. Subjects were assigned to an experimental group (n=24) and to a control group (n=26). Both groups were taught same materials by the same teacher. The critical thinking activities were manipulated into the experimental group, whereas the control group received no critical thinking activities. Pre and post tests of knowledge monitoring were obtained. Subjects took an academic test at the end of the experiment. The results demonstrated that knowledge monitoring in experimental group significantly improved. Significant differences were found between pre and post knowledge monitoring in the experimental group. Recommendations and suggestions are discussed.